Suspended CNTs/MoS2 heterostructure field effect transistor for high performance biosensor and its application for serum PSA detection - Wei, Junqing; Liu, Zihao; Zhang, Zhuyu; Lan, Kuibo; Wang, Yong; Chen, Ruibing; Qin, Guoxuan (Sensors and actuators. B, Chemical, 2023)
Field effect transistor (FET) biosensors provide highly sensitive and rapid detection of bioactive proteins and biomarkers. However, the interface scattering may degrade device performance and the supported substrate also limits the exposed area to biological analytes. Here, a suspended heterostructure field effect transistor (FET) was fabricated for the detection of prostate specific antigen (PSA) in clinical serum samples from patients with prostate cancer. First, we tested the performance of the biosensor by β-actin detection, and the suspended CNTs/MoS2 heterostructure FET showed higher mobility, conductivity and sensitivity with enhanced stability compared to the conventional supported MoS2 FET. Furthermore, the suspended device showed ultrasensitive detection of PSA with the limit of detection (LOD) as low as 10-13 μg/μL and large detection range from 10-13 to 10-4 μg/μL. The device also showed rapid response and higher stability. For clinical application, multiple serum samples were analyzed by the suspended CNTs/MoS2 FET biosensors. The PSA concentration measured by the device was highly consistent with those obtained by the enzyme-linked immunosorbent assays (ELISA) method. Taken together, the suspended CNTs/MoS2 FET showed sensitive and reliable detection capability with great potential for rapid clinical examination and biomarker monitoring. •This study demonstrates screening PSA by using semiconductor electronics.•The suspended CNTs/MoS2 heterostructure FET are fabricated with high mobility and good bio-sensing performances.•The novel biosensors exhibit high sensitivity with LOD= 10-12 μg/μL for β-actin and 10-13 μg/μL for PSA detection.•This biosensors enable a rapid quantification of PSA level in prostate cancer patients and healthy people.